Elevated carbon dioxide and nitrogen supply affect photosynthesis and nitrogen partitioning of two wheat varieties. (21st July 2019) - Li, Ping; Hao, Xingyu; Aryal, Mela; Thompson, Michael; Seneweera, Saman
Abstract: The response of wheat to elevated carbon dioxide concentration (e[CO2 ]) is likely to be dependent on nitrogen supply. To investigate the underlying mechanism of growth response to e[CO2 ], two wheat cultivars were grown under different carbon dioxide concentration [CO2 ] in a chamber experimental facility. The changes in leaf photosynthesis, C and N concentration, and biomass were investigated under different [CO2 ] and N supply. The result showed an increase in photosynthesis under e[CO2 ] at all N level except the one with the lowest N supply. Furthermore, a significant decrease in g s and Tr for both the cultivars was also observed under e[CO2 ] at all N levels. A considerable increase in WUEi was observed for both the cultivars under e[CO2 ] at all N levels except for the lowest concentration one. Therefore, the study shows that a stimulation of plant growth under e[CO2 ] to be marginal at higher N supply.